Detection of Legionella pneumophila bacteria from water sources in Palembang City, Indonesia (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Kautsar R, Fauziyah S, Aquaresta F, Widya AM, Fajar NS, Damayanti M, Sucipto TH. 2024. Detection of Legionella pneumophila bacteria from water sources in Palembang City, Indonesia. Biodiversitas 25: 1499-1504. Legionella is a pathogenic bacterial genus that causes legionellosis. This bacteria is a gram-negative bacteria which is often found in warm and humid aquatic environments. Legionella spp. infection occurs due to inhalation of aerosols contaminated with Legionella spp. Until now, legionellosis is still a crucial public health problem in the world. Therefore, it is necessary to take preventive measures to detect the presence of Legionella spp. as early as possible. This study aimed to detect the presence of Legionella pneumophila from well water samples and drinking water sources in Palembang City using the Nested PCR method. The primers used in this study are specific primers that amplify the mip gene. The PCR amplification results showed that 2 of the 22 samples were positively contaminated with L. pneumophila. These positive samples came from well water and drinking water samples. Based on physical parameters, all samples are still safe for consumption because they have a normal temperature, are odorless and clear. Meanwhile, based on chemical parameters, the pH of all samples is still safe for consumption because it is still below the maximum threshold.
Keywords: Drinking water supply system, Legionella pneumophila, legionellosis, mip gene, nested PCR